The Implementary of Inquiry Learning in Middle School in Masaran - Linda Ochtivah W; Baskoro Adi P; Ashadi Ashadi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The application of inquiry based learning is important to be developed in education because it trains the students to investigate a problem and find the solution of it. The aim of this research is to investigate the implementation of inquiry based learning in the learning process at the middle school in Masaran. This research belongs to qualitative research. The techniques of collecting the data used are observation and deep interview with Science teacher of SMP Negeri 1 Masaran. Miles & analyse Huberman was analyzing the obtained data. The data in this research are divided into two sub topic, the instructional process done by the teacher and the use of infrastructure supporting the instructional process. The result shows that the instructional process in SMP N 1 Masaran has not implemented the inquiry based learning optimally. Regarding the teacher perception, the time allocation is limited to cover all the activities consisted of this learning model. The other finding dealing with the second topic is the infrastructures in this school are not utilised in the instructional process. The cause is similar to the former. The time allotment given is not sufficient to complete the basic competence that should be gained.